Implementasi Vector Space Model untuk Pencarian Jurnal Ilmiah (Studi Kasus E-jurnal Universitas Stikubank Semarang) (Information Technology and Telematics, 2014)
Abstract -- Nowadays a lot of scientific journals have been published in the internet media. It aims to search information easier. Scientific journals have information that can be used as a reference in the new study and to prevent plagiarism. Internet media has several search engines but they generate many results and less specific enough. Implementation of vector space model in information retrieval systems are made in this study. Method of vector space model using vector space is to see a resemblance between the document and keywords. Similarity calculation result shows more attention to emergence of a term in a document (term frequency) and in the collection of documents (invest document  frequency). So It will make the search  more accurate with more specific results. Keywords -- Vector space model, information retrieval system, scientific journal.